Hymenoptera stings: a study of clinical profile, complication and outcome from a teaching hospital of central Nepal - Ghimire, M; Pahari, B; Paudel, N; Das, G; Sharma, SK; Das, G (Journal of College of Medical Sciences-Nepal, 2014)
Background Hymenoptera sting is a common health hazard in the tropics. Wasp and Bee stings can produce symptoms ranging from local allergic reactions to serious complications including anaphylaxis and multiple organ dysfunction syndromes. Objective To evaluate the clinical profile, management and early outcome of patients with gallbladder cancer. Methods We prospectively analyzed all the consecutive patients with Hymenopterid sting (Wasp and Bee stings), who were admitted in Nephrology Unit in college of Medical Sciences Teaching hospital over a period of two year; from June 2010 to May 2012. Data including demographic profile, clinical profile, complications and outcomes associated with the Hymenopterid stings were entered in a designated profroma and were analyzed. Results A total of 15 cases with Hymenopterid stings (Wasp and Bee stings) were analyzed. Majority of the cases were females (n=8). The male to female ratio was 0.88. The mean age of the case was 37.1± 17.38years. Most of the cases (n=11) were younger subjects d"45 years and majority of them felt in the age group of 21-30 years; (n=4). Mean number of stings (Wasp or Bee stings), were 46 ± 18.4 (12-74) and the mean time to reach the hospital from the bite time was 78.23±82.24 hours (30 minutes-13 days). Black Wasps were the commonest species to inflict the stings in (n=10) cases and Bees in (n=5) cases. The Hymenoptera stings were observed more frequently in the month of July to September in (n=8). The commonest site of bite was head and face seen in (n=11) cases. Among the clinical presentations the commonest clinical presentation was local burning pain and pruritus which was present in all the cases (n=15) followed by nausea (n=10). The commonest clinical sign was bipedal edema which was seen in (n=7) cases. Low Hb (defined as Hb <10gm/dl) was seen in (n=5) cases of Hymenopterid stings. Low platelet (defined as Platelet < 100X109/L) was documented in (n=10) cases. Serum creatinine >1.5mg /dl was seen in (n=7) cases. Low serum albumin (defined as Serum Albumin (<3.5gm/dl) was seen in (n=6) cases. Among the complications, the most common complication was Hepatitis which was seen in (n=9) cases, followed by Acute Kidney Injury. There was no mortality associated with Hymenopterid stings in our study. However 1 patient left against medical advice. Conclusion Black Wasps were the commonest species to inflict the stings in (n=10) cases. The most common complication of Hymenoptera sting was Hepatitis, which was seen in (n=9) of cases, followed by Acute Kidney Injury. Majority of complications were seen in Wasp stings which caused significant morbidity. No mortality was observed in our study except one case; that left hospital against medical advice. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 17-24